From Contractual Breach to Corporate Criminal Liability: Exploitation of Debtor Data by Account Officers in Indonesia - Afif Muhni; Muhammad Basri; Syarif Saddam Rivanie; Nuriyah Fara Muthia; Ulil Amri (JUSTISI, 2026)
The aim of this study is to analyze criminal liability for data exploitation committed by an AO in order to establish corporate liability against the receiving bank. The method used in this study is a normative approach with legal and conceptual perspectives. This study analyzes the shift in the nature of illegality from a breach of contract to criminal data exploitation. The novelty of this study demonstrates that recipient banks, which derive economic benefits from such illegal data, qualify as Beneficial Owners subject to corporate criminal liability under the doctrine of Vicarious Liability. The results of this study indicate that the transfer of data without specific written consent constitutes a criminal offense under Article 65(2) of the Personal Data Protection Act. Conclusion This study recommends the establishment of criminal policies based on Economic Analysis of Law, applying cumulative sanctions: imprisonment for individuals and substantial administrative fines for corporations. This step is crucial to eliminate the economic incentives behind data crimes and ensure legal certainty in the digital banking environment.